(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Diabetic ketoacidosis (DKA) is a serious, acute complication of type 1 diabetes mellitus, characterized by hyperglycemia, metabolic acidosis, and ketonemia. Despite advances in insulin therapy, DKA remains a common cause of hospitalization and mortality. Identifying the precipitating factors is essential for prevention, early intervention, and improving patient outcomes. Objectives: The study aimed to assess the frequency of precipitating factors contributing to diabetic ketoacidosis in patients with type 1 diabetes and to analyze demographic and clinical associations influencing the occurrence of DKA. Study design: retrospective observational study. Place and duration of study: From July 2024 to December 2024, Department of General Medicine Sandeman Provincial Hospital / Bolan Medical College / Hospital Quetta, Balochistan. Methods: This retrospective observational study included 120 patients with type 1 diabetes mellitus admitted with diabetic ketoacidosis over a two-year period. Data were collected from hospital records, including demographic details, clinical presentation, precipitating factors, and laboratory results. Statistical analysis was performed to determine mean age, standard deviation, and p-values for associations between risk factors and DKA. Ethical clearance was obtained prior to study initiation. Results: A total of 120 patients with type 1 diabetes presenting with diabetic ketoacidosis were analyzed. The mean age of patients was 22.4 ± 6.8 years. The most common precipitating factor was infection (38%), followed by insulin omission (32%), new diagnosis of diabetes (20%), and medical/surgical stress or other causes (10%). A significant association was observed between infection and severity of DKA (p < 0.05). Insulin omission was more frequent among adolescents and young adults compared to other age groups (p < 0.01). Gender was not significantly associated with precipitating factors (p > 0.05). Conclusion: Infections and insulin omission remain the leading precipitating factors for diabetic ketoacidosis in type 1 diabetes patients. Early recognition of these risk factors and improved patient education may reduce the incidence of DKA. Targeted interventions, including infection control strategies and reinforcement of insulin adherence, should be prioritized in high-risk groups to minimize complications and healthcare burden.